Measuring patients’ experience of nursing quality in acute hospitals: review of existing scales and development and psychometric validation of a new scale - Blume, Kai Svane; Kirchner-Heklau, Uta; Winter, Vera; Meyer, Gabriele; Fleischer, Steffen (BMJ open, 2024)
ObjectiveTo provide an overview of existing instruments measuring patient-perceived quality of nursing care and to develop and psychometrically evaluate a new multidimensional scale applicable to the German acute care sector.DesignWe conducted a scale development and validation study involving the following phases: (1) performing a structured literature search to identify existing scales, (2) generating an initial pool of items using the results of the literature search and expert interviews, (3) coding/categorising the item pool, (4) organising a peer researcher workshop to select relevant items, (5) drafting the survey questionnaire and conducting cognitive pretesting, (6) pilot testing the survey questionnaire, (7) administering the survey to a large sample of hospital patients and (8) conducting a psychometric evaluation comprising exploratory factor analysis using the survey results, followed by confirmatory factor analysis and reliability and validity assessment of the resulting draft scale.Survey participants17 859 recently hospitalised patients discharged from non-intensive care in non-paediatric and non-psychiatric hospital units in Germany between May and October 2019.ResultsWe identified 32 instruments comprising 635 items on nursing care quality. Alongside 135 indicators derived from expert interviews, these formed our initial item pool, which we coded into 15 categories. From this pool, 36 items were selected in the peer researcher workshop for pretesting and psychometric evaluation. Based on the results of our exploratory and confirmatory factor analyses, we propose a second-order scale to measure Patients’ Experience of Nursing Quality in Acute Hospitals (PENQuAH), including the two higher-order dimensions ‘patients’ perception of direct nursing care activities’ and ‘patients’ perception of guidance provided by nurses’. The results of various tests suggest the scale has sufficient goodness of fit, reliability and validity.ConclusionsThe PENQuAH scale is promising in terms of its psychometric properties, the plausibility and meaningfulness of its dimensions, and its ease of use.